Recursive Identification for Hammerstein Systems with State-space Model - CHEN, Xi; FANG, Hai-Tao (Zi dong hua xue bao, 2010)
In this paper, the subspace methods for multi-input multi-output (MIMO) Hammerstein systems in state-space form are considered, for the reason that relation of input and output in MIMO case is appropriate to indicate in this form. In open-loop case, a subspace identification method is given for Hammerstein systems, in which the nonlinear static function can be represented as a linear combination of finite basis functions, and the recursive version of this method is also given. We show that, in mild conditions, the method given in this paper is consistent in some sense. A numerical example is given to show the performance of this method.